KEPATUHAN PERAWAT DALAM PENERAPAN SURGICAL SAFETY CHECKLIST SEBAGAI UPAYA PENCEGAHAN KESALAHAN TINDAKAN OPERASI DI UNIT OPERATING THEATRE DAN CATHLAB: SUATU LITERATUR REVIEW - Elly Dwi Krisnawati; Yusmy Putra Azahrul Umam (CV. ADIBA AISHA AMIRA, 2025)
Background: The Surgical Safety Checklist (SSC) is a tool developed by the WHO to improve patient safety during surgical procedures. Nurses play a central role in the implementation of SSC in operating rooms and cath labs. However, compliance with SSC varies across institutions, necessitating a systematic review of its implementation effectiveness. Objective: To systematically review the literature on nurse compliance with SSC implementation and its association with the prevention of surgical errors in operating theatres and cath labs. Method: This study is a literature review examining 10 articles published in the last five years (2019–2024). Articles were collected through searches in the PubMed, Google Scholar, and Semantic Scholar databases using keywords related to SSC, nurse compliance, and patient safety. Inclusion criteria included quantitative or review articles relevant to the focus on the role of nurses. Results: The synthesis of findings indicates that nurse compliance with SSC is positively correlated with improved patient safety and reduced adverse events. Some studies demonstrate that SSC can significantly reduce complications and mortality. Factors such as knowledge, training, safety culture, and managerial support influence nurse compliance in implementing SSC. Conclusion: Nurse compliance with SSC implementation is crucial in preventing surgical errors. Continuous interventions such as training, supervision, and strengthening safety culture are needed to enhance the effectiveness of SSC implementation in operating theatres and cathlabs.